Influence the number of laser pulses and annealed temperature and the Structure and optical properties of In2O3: CdO films prepared laser induce plasma - Aadim, Kadhim A.; Abbas, Nada K.; Dahham, Ashwaq T. (Iraqi Journal of Science, 2018)
In this Research, (In2O3: CdO) films were prepared using pulsed laser deposition (PLD) method on glass substrate at room temperature deposited at laser influence 500mJ/cm2with different shoots N= (200,300,400,500and600). the structural, and the optical properties and the films are studied with different annealing temperatures (523and 623) K. Optical measurements and the films were analyzed by UV-VIS absorption spectra. The structural properties of samples were investigated by x-ray diffraction patterns of the films and show that the films and polycrystalline Structure with all shoots. Transmittance spectrum found is equal to 93.17%, refractive index range is 1.635 and energy gap range is 2.75-3.15ev.